The United States of Europe : the new superpower and the end of American supremacy - Reid, T. R. (New York : Penguin Books, 2005)
To Americans accustomed to unilateralism abroad and social belt-tightening at home, few books could be more revelatory--or controversial--than this timely, lucid, and informative portrait of the new European Union. Now comprising 25 nations and 450 million citizens, the EU has more people, more wealth, and more votes on every international body than the United States. It eschews military force but offers guaranteed health care and free university educations. And the new "United States of Europe" is determined to be a superpower. Tracing the EU's emergence from the ruins of World War II and its influence everywhere from international courts to supermarket shelves, T.R. Reid explores the challenge it poses to American political and economic supremacy. The United States of Europe is essential reading. -- Distributed by Syndetic Solutions, LLC.
Prologue: Sleeping through the revolution -- The Atlantic widens -- The invention of peace and the pursuit of prosperity -- The almighty undollar -- Welch's Waterloo -- L'Europe qui gagne; or, I can't believe it's not American butter -- The European social model -- Showdown at capability gap -- Generation E and the ties that bind the new Europe -- Waking up to the revolution -- APPENDIX 1: The states of Europe -- APPENDIX 2: Inside the belgeway: the governing structure of the European Union.
Includes bibliographical references (pages 288-289) and index.
Keywords: European Union -- History; Great powers; European Union countries -- Relations -- United States; United States -- Relations -- European Union countries; International relations; United States; History